The Communicative Body’s Call for Prospective Organ Donors: Montefiore Health System’s “Live and Let Live” Digital Platform - Chong, Nancy (Ars Medica, 2023)
More than 100,000 people are on the national transplant waiting list for a liver or kidney, and about 20 percent of those are in need to find a living donor.